Crystal structure of salmeterol xinafoate form I (Serevent®Diskus®), (C25H37NO4)(C11H8O3). Issue 4 (11th November 2015) - Kaduk, James A.; Zhong, Kai; Gindhart, Amy M.; Blanton, Thomas N.
Abstract : The crystal structure of salmeterol xinafoate has been solved and refined using synchrotron X-ray powder diffraction data, and optimized using density functional techniques. Salmeterol xinafoate crystallizes in space group P− 1 (#2) with a = 9.173 89(13), b = 9.483 79(14), c = 21.3666(4) Å, α = 82.2646(13), β = 85.2531(12), γ = 62.1565(11)°, V = 1628.37(5) Å 3, and Z = 2. Key to the structure solution was linking the two fragments by a Li atom along the expected N–H···O hydrogen bond. The salmeterol cation and xinafoate anion are linked by N–H···O and O–H···O hydrogen bonds, interactions which cause the salmeterol to adjust its conformation. The hydrogen bonds result in complex chains along the b -axis. The powder pattern is included in the Powder Diffraction File ™ as entry 00-065-1430.